2022
DOI: 10.1007/s11739-022-02958-2
|View full text |Cite
|
Sign up to set email alerts
|

Circulating biomarkers in diagnosis and management of cardiac amyloidosis: a review for internist

Abstract: Cardiac amyloidosis (CA) is due to extracellular myocardial deposition of misfolded proteins resulting in severe cardiac dysfunction and death. The precursors of amyloid fibrils, able of determining a relevant cardiac infiltration, are immunoglobulin-free light chains (AL amyloidosis) and transthyretin (TTR) (both wild and mutated types). The diagnosis of amyloidosis represents a challenge for the clinician given its rarity and its protean clinical presentation, thus an early diagnosis remains a cornerstone fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 87 publications
1
7
0
2
Order By: Relevance
“…Thus, there is a great unmet medical need for early diagnosis of amyloid cardiac involvement. Our study found that advanced NYHA grade, high BNP and myocardial injury markers, low eGFR, and high E/E' are all potential risk factors for poor prognosis and these factors also play an important role in staging the disease, guiding treatment and prognostic assessment ( 31 , 32 ), which is also consistent with current clinical knowledge. With regard to CMR, the important value of LGE in assessing the prognosis of CA patients has been reaffirmed.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, there is a great unmet medical need for early diagnosis of amyloid cardiac involvement. Our study found that advanced NYHA grade, high BNP and myocardial injury markers, low eGFR, and high E/E' are all potential risk factors for poor prognosis and these factors also play an important role in staging the disease, guiding treatment and prognostic assessment ( 31 , 32 ), which is also consistent with current clinical knowledge. With regard to CMR, the important value of LGE in assessing the prognosis of CA patients has been reaffirmed.…”
Section: Discussionsupporting
confidence: 87%
“…As such, early detection is paramount to prevent systemic complications and to initiate therapeutic interventions in a timely fashion. Amyloidosis workup is comprehensive with inclusion of clinical presentation, serologic testing, non-invasive imaging, and biopsy with histopathology testing [2,4].…”
Section: Diagnosismentioning
confidence: 99%
“…Progression of symptoms to other organs is not uncommon, so patients require close follow-up and monitoring to assess for noncardiac involvement, including ophthalmologic, neurologic, and gastrointestinal screening [1]. Once a diagnosis of ATTR amyloidosis is suspected, biomarkers such as natriuretic peptides and high-sensitivity plasma troponin T (hsTnT) levels play a useful role as clinical indicators for disease progression and as predictors for survival [2]. In fact, studies have shown that cutoffs of 3000 pg/mL and 0.05 ng/mL for NT-proBNP and hsTnT, respectively, help stratify mortality risk in ATTR amyloidosis patients [9].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…NT-proBNP и тропонины повышаются у пациентов с ИЗС вследствие инфильтративного процесса в миокарде или прямого токсического воздействия аномальных веществ на кардиомиоциты. В одном исследовании среди пациентов с AL-амилоидозом сердца уровень NT-proBNP никогда не был ниже 97,5 процентиля для нормальных людей, что указывает на 100% чувствительность; более того пороговое значение NT-proBNP 1285 нг/л имело точность 92% для выявления поражения сердца [26]. NT-рrоBNP может служить ранним индикатором диастолической дисфункции ЛЖ у пациентов с перегрузкой железом, БФ [15,23].…”
Section: лабораторные данные сердечные биомаркерыunclassified